Governance of research and product improvement studies in consumer mental health apps. Interviews with researchers and app developers - Verbeke, Kamiel; Jain, Charu; Shpendi, Ambra; Borry, Pascal (Accountability in research, 2025)
Consumer mental health apps (MHAs) collect and generate mental health-related data on their users, which can be leveraged for research and product improvement studies. Such studies are associated with ethical issues that may be difficult for researchers and app developers to assess. To improve ethical study conduct, governance through rules, agreements and customs could be relied upon, but their translation into practice is subject to barriers. This qualitative interview study with 17 researchers and app developers looked into the role and impact of governance standards on consumer MHA studies. Interviewees experienced a significant number of rules, agreements and customs, although not all of the governance standards that can potentially be applicable. Standards did have an impact on the interests of researchers and app developers, app users and society, but this impact was mediated by several barriers related to their conceptualization and implementation. Conceptualization barriers impacted the development of a standard, the inclusion of relevant concepts and the coordination between standards. Implementation barriers concerned the resource cost of understanding a standard, as well as suboptimal enforcement. The framework developed in this study can support more effective efforts to improve the governance of future consumer MHA studies.